College Students’ Perspectives on Creating Plant Anatomy and Physiology Worksheets in The View of Constructivism Theory - Harsi Admawati; Nur Balqis Mutia (Universitas Tidar, 2023)
The aim of this study was to explore college students’ perspectives on creating worksheets for Junior High School students. Plant anatomy and physiology were used as the topic of the project. The participants included 30 undergraduate students in the 5th semester of the Science Education Study Program who took the Anatomy and Physiology of Living Things course at the Faculty of Teacher Training and Education, Tidar University. Open-ended questions were applied to gather students' perceptions of the project. Moreover, the data on college students’ satisfaction with the course and the instructor were taken through a questionnaire. The result of this study showed creating students’ worksheets gave beneficial effects even though some obstacles should be handled during the process. In the other side, students were satisfied with the project. Based on the constructivism theory, this student-centered learning process gave a wide opportunity for college students to construct knowledge and meaning from their experiences in the creation of student worksheets. The findings of this study can be used as considerations regarding learning strategies to improve classroom practices.